A Field Study on Group Housing of Lactating Sows with Special Reference to Sow Health at Weaning - Hultén, F. (Acta Vet Scand, 1995)
Four farms that group-housed sows from 2 weeks of lactation until weaning (G-farms) and 3 farms that kept the sows individually penned throughout the 5 to 6-week-long lactation period (C-farms), were compared in terms of sow health. All sows were crossbred Swedish Yorkshire × Swedish Landrace. The daily food ration was similar on all farms except during the group-housing period, when G-farm sows were fed ad libitum. Sows were grouped in the breeding section and kept grouped on deep litter in the dry sow section on all farms. Individual health examinations were performed at the time of weaning (±4 days) on 179 G-farm sows and on 167 C-farm sows. Teat- and udder skin wounds occurred less frequently (p<0.001) in G-farm sows than in C-farm sows. In addition, preweaning atrophy of all mammary glands occurred in 6.6% of the G-farm-sows but not in a single C-farm sow (p<0.001). This indicates that sow-piglet interactions decrease when sows are group housed. However, these differences did not occur in primiparous sows, suggesting that the relation between the primiparous sow and her litter is not affected. Mastitis frequency was the same in the 2 systems. Moreover, the frequency of locomotor disorders was the same in the 2 groups, and hoof overgrowth was common in both systems. These similarities could be due to the fact that all farms group housed dry sows on deep litter. A strong relation (p<0.001) between hoof overgrowth and locomotor disorders was evident. Low access to food due to low rank among primiparous group-housed sows was indicated by a lower (p<0.05) backfat thickness compared with multiparous sows, and a higher (p<0.001) frequency of skin wounds compared with individually housed primiparous sows.